2021
DOI: 10.23736/s1973-9087.21.06915-x
|View full text |Cite
|
Sign up to set email alerts
|

What does evidence tell us about the use of gait robotic devices in patients with multiple sclerosis? A comprehensive systematic review on functional outcomes and clinical recommendations

Abstract: INTRODUCTION: There is growing evidence on the efficacy of gait robotic rehabilitation in patients with multiple sclerosis (MS), but most of the studies have focused on gait parameters. Moreover, clear indications on the clinical use of robotics still lack. as part of the cicEroNE italian consensus on robotic rehabilitation, the aim of this systematic review was to investigate the existing evidence concerning the role of lower limb robotic rehabilitation in improving functional recovery in patients with Ms. EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…1 Another important aspect to consider before we start the widespread use of exoskeletons in MS relates to the specific patient subgroup that may benefit. Indeed, it is suggested that clinical effects of robot-assisted gait training are superior to conventional treatment in severely (but not in moderately) affected people with MS. 1,2 These results were implemented in the figure published by Calabro et al, 3 where patients gait deficits (based on Expanded Disability Status Scale (EDSS) scores) were plotted relative to the type of the therapy and devices (from overground walking training to powered exoskeletons to grounded exoskeletons).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Another important aspect to consider before we start the widespread use of exoskeletons in MS relates to the specific patient subgroup that may benefit. Indeed, it is suggested that clinical effects of robot-assisted gait training are superior to conventional treatment in severely (but not in moderately) affected people with MS. 1,2 These results were implemented in the figure published by Calabro et al, 3 where patients gait deficits (based on Expanded Disability Status Scale (EDSS) scores) were plotted relative to the type of the therapy and devices (from overground walking training to powered exoskeletons to grounded exoskeletons).…”
mentioning
confidence: 99%
“…2 Combination of exoskeleton therapy with virtual reality, can increase the impact on motor and non-motor outcomes such as psychological well-being and quality of life. 3,8 Third, although there is progress related to the usability of exoskeletons there is still a lot of improvement possible. For stationary and mobile exoskeletons, patients and therapists reported high levels of satisfaction.…”
mentioning
confidence: 99%
“…Therefore, RAR combined with CPT offers some valuable clinical benefits. Contrarily, other studies showed no significant difference between RAR and CPT [ 9 , 10 , 11 , 12 , 40 ]. Therefore, further investigation is necessary to find additional strategies to RAR that may further promote rehabilitation outcome achievement.…”
Section: Discussionmentioning
confidence: 88%
“…Many promising RAR interventions have been shown to improve the mobility, function, and quality of life of individuals with SCI, in particular regarding lower extremity robotic exoskeletons. However, the majority of the available works have methodological and rehabilitation paradigm differences, thus being unable to demonstrate the superiority of one gait training strategy over another in counteracting the loss of muscle strength and trophism, walking disability and mobility, sensory dysfunction, autonomic disorders, spasticity, pain, and overall quality of life [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Therefore, more extensive studies are required to prove RAR’s benefits definitively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, different authors have attempted to demonstrate the clinical efficacy of robotics in patients with MS, mainly focusing on motor outcomes. [7][8][9] In their recent systematic review, Bowman et al found that RAGT, provided with exoskeleton devices, improves balance and gait outcomes in a clinically meaningful way, thanks to their several advantages in terms of safety, motor assistance, and intensity of training. Then, the authors concluded that RAGT should be used in patients with MS and severe disability in a multimodal rehabilitation context as an opportunity to maximize their functional recovery.…”
mentioning
confidence: 99%